MEKANISME PEMBERHENTIAN KEPALA DAERAH DAN/ATAU WAKIL KEPALA DAERAH MENURUT UNDANG-UNDANG TENTANG PEMERINTAHAN DAERAH TAHUN 1974-2014 - Muhammad Syahwalan (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: The problems of Regional autonomy with a centralistic tendency is incarnated in the mechanism of dismissal of regional heads according to Act No. 32 of 2004. A new regional government law has emerged, namely Act No.  9 of 2015 concerning the Second amendment of Act No. 23 of 2014 about Regional Government. This research is a type of normative juridical research with primary sources of regional government laws. The results of the study show that the dismissal of regional heads and/or deputy regional heads is carried out by the DPRD leadership to the President. This proposal is obtained from a series of supervisory processes. If the DPRD leadership is not able to carry out this task, the proposal will be made by the Minister of Home Affairs. The political nuance of each law issued above has an influence on the flexibility of legal ideals to create autonomous regions. The freedom of the region to take care of its own region independently slowly reaches its way until the Act No. 23 of 2014 has been fairly proper in representing the ideals of the region to become more independent and carry out the broadest autonomy in accordance with the constitutional mandate. Keywords: Impeachment Mechanism, Regional Head, Regional Government.